2020
DOI: 10.1155/2020/6802905
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Multimodal Biometrics Using the Face and Ear

Abstract: In the recent years, we have witnessed the rapid development of face recognition, though it is still plagued by variations such as facial expressions, pose, and occlusion. In contrast to the face, the ear has a stable 3D structure and is nearly unaffected by aging and expression changes. Both the face and ear can be captured from a distance and in a nonintrusive manner, which makes them applicable to a wider range of application domains. Together with their physiological structure and location, the ear can rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…What needs to be done to overcome this is to extract features and synthesize faces simultaneously because both provide mutual benefits to each other [8]. The ear in face detection has a fairly good level of stability in the 3D structure and is almost not affected by aging and changing facial expressions [71]. Meanwhile, determining racial and ethnic requires a database containing the characteristics of each racial and ethnic group based on facial features, expressions, gender and so on [72].…”
Section: What Are the Essential Facial Features Used For Face Recogni...mentioning
confidence: 99%
“…What needs to be done to overcome this is to extract features and synthesize faces simultaneously because both provide mutual benefits to each other [8]. The ear in face detection has a fairly good level of stability in the 3D structure and is almost not affected by aging and changing facial expressions [71]. Meanwhile, determining racial and ethnic requires a database containing the characteristics of each racial and ethnic group based on facial features, expressions, gender and so on [72].…”
Section: What Are the Essential Facial Features Used For Face Recogni...mentioning
confidence: 99%
“…Ear and face features can be used as complementary information in multimodal biometric systems, as both can be captured simultaneously in a single scan. This integration enhances recognition accuracy, frequently in surveillance and tracking applications [6]. For these reasons, more and more research is being conducted into the application of ear recognition in various fields, such as security, surveillance and forensics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ear recognition systems can complement other biometric modalities, providing identification clues when information from other sources is unreliable or unavailable. Recent studies have demonstrated the importance of ear recognition technology in multimodal biometric systems (Sarangi et al, 2018;Sarangi et al, 2022;Ma et al, 2020;Maity et al, 2020). While ear recognition offers many advantages, it also faces challenges that can impact the recognition process.…”
Section: Introductionmentioning
confidence: 99%